2013
DOI: 10.1002/phar.1270
|View full text |Cite
|
Sign up to set email alerts
|

Reversal of Oral Anticoagulation

Abstract: Although the use of dabigatran and rivaroxaban are increasing, data on reversal of their effects are limited. The lack of reliable monitoring methods and specific reversal agents renders treatment strategies empirical and as a result, , treatment consists mainly of supportive measures. Therefore, we performed a systematic search of the PubMed database to find studies and reviews pertaining to oral anticoagulation reversal strategies. This review discusses current anticoagulation reversal recommendations for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
28
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 90 publications
(177 reference statements)
0
28
0
Order By: Relevance
“…Second, there are no direct acting antidotes for either dabigatran or any of the FⅩa inhibitors. Nevertheless, recommendations have been made in treatment guidelines regarding how to manage anticoagulation reversal of the new agents, and several recent reviews on the topic have been published [91][92][93] . Moreover, some groups have offered consensus expert opinions by the authors regarding optimal approaches for anticoagulation reversal of the new agents [93,94] .…”
Section: Reversal Of Tsoasmentioning
confidence: 99%
See 4 more Smart Citations
“…Second, there are no direct acting antidotes for either dabigatran or any of the FⅩa inhibitors. Nevertheless, recommendations have been made in treatment guidelines regarding how to manage anticoagulation reversal of the new agents, and several recent reviews on the topic have been published [91][92][93] . Moreover, some groups have offered consensus expert opinions by the authors regarding optimal approaches for anticoagulation reversal of the new agents [93,94] .…”
Section: Reversal Of Tsoasmentioning
confidence: 99%
“…The thrombin time (TT) test is affected by dabigatran but is very sensitive to the drug effects, rendering it a qualitative measure at typical drug concentrations. However, it can be used to exclude a dabigatran drug effect [92,95,96] . Liew et al [96] suggested a normal aPTT result combined with a prolonged TT indicated low anticoagulation intensity with dabigatran, whereas prolonged results for both tests would indicate full anticoagulation.…”
Section: Anticoagulation Monitoring Of Tsoasmentioning
confidence: 99%
See 3 more Smart Citations